Encontros e outras andanças: experimentações em uma educação (matemática) - JOAO PAULO RISSO (2025)
The present research aims to build experiments in thought as invitations to Mathematics teachers (both active and in training) to not ignore the injustices of our time, engage in struggles and social projects, and become militant teachers. We will present in the following lines a thesis-novel-manifesto that accompanies the life of the character João, a doctoral student in Mathematical Education. With it, which can be considered an experiment that fits within the interface between Literature, Philosophy of Difference, Education (Mathematics), and other fields, we mobilize some concepts and ideas from Gilles Deleuze, Félix Guattari, Silvio Gallo, bell hooks, Clarice Lispector, Ubiratan D’Ambrosio, Carolina Maria de Jesus, Buchi Emecheta, and other authors and writers. Our intention is to engage in dialogue, compose, and overflow lives with the data produced in the second semester of 2021, considering the method of Cartography and in the context of a Teaching Practice course in a Mathematics degree at a public university in Mato Grosso do Sul. The classes of this discipline took place via Google Meet and were recorded and transcribed by the researchers. Some themes discussed in the data production and addressed in the thesis-novel-manifesto were: social inequality, religious intolerance, ethics, punishment, assessment, family relationships, friendship, abortion, legality and illegality, class, gender, race, morality, and others. As in other works, through this thesis-novel-manifesto, we extend our invitation to you, dear readers, to experiment with literature, desire and affection.